1997
DOI: 10.1212/wnl.49.6.1513
|View full text |Cite
|
Sign up to set email alerts
|

Changes of hippocampal N-acetyl aspartate and volume in Alzheimer's disease

Abstract: Hippocampal atrophy detected by MRI is a prominent feature of early Alzheimer's disease (AD), but it is likely that MRI underestimates the degree of hippocampal neuron loss, because reactive gliosis attenuates atrophy. We tested the hypothesis that hippocampal N-acetyl aspartate (NAA: a neuronal marker) and volume used together provide greater discrimination between AD and normal elderly than does either measure alone. We used proton MR spectroscopic imaging (1H MRSI) and tissue segmented and volumetric MR ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
12

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(147 citation statements)
references
References 16 publications
4
129
0
12
Order By: Relevance
“…First, the magnitude of the NAA reduction is very similar to that, which we previously reported for patients with Alzheimer's dementia (20) . Notwithstanding this similarity of NAA reductions, our PTSD patients showed no gross cognitive memory impairments.…”
Section: Naa In Post Traumatic Stress Disorder (Ptsd)supporting
confidence: 86%
See 1 more Smart Citation
“…First, the magnitude of the NAA reduction is very similar to that, which we previously reported for patients with Alzheimer's dementia (20) . Notwithstanding this similarity of NAA reductions, our PTSD patients showed no gross cognitive memory impairments.…”
Section: Naa In Post Traumatic Stress Disorder (Ptsd)supporting
confidence: 86%
“…Notwithstanding this similarity of NAA reductions, our PTSD patients showed no gross cognitive memory impairments. Second, hippocampal NAA reductions in Alzheimer's disease were accompanied by substantial hippocampal volume losses in the range from 20% to 40% (20) . Another explanation for NAA decrease in PTSD is impaired metabolism of neuronal processes, resulting in secondary NAA loss.…”
Section: Naa In Post Traumatic Stress Disorder (Ptsd)mentioning
confidence: 98%
“…Consequently, it has been suggested that decrease in NAA values may also reflect the magnitude of neuronal injury and metabolic dysfunction. Decrease in NAA in the hippocampus has been reported in several conditions, including PTSD (Schuff et al, 1997a), epilepsy (Ende et al, 1997), Alzheimer's disease (Schuff et al, 1997b) and normal aging (Driscoll et al, 2003a(Driscoll et al, , 2005Schuff et al, 1999).…”
Section: Biochemical Changesmentioning
confidence: 99%
“…In the manual method, boundaries of the hippocampus were drawn on the T1-weighted MR images using in-house-written software (19), following previously published guidelines that include the hippocampal proper, dentate gyrus, subiculum, fimbria, and alveus (20). Volumes were calculated by counting all pixels within the traced area and multiplying by the nominal MRI resolution.…”
Section: Volume Measurementsmentioning
confidence: 99%